TINJAUAN YURIDIS TERHADAP PRAPERADILAN SEBAGAI UPAYA KONTROL BAGI PENYIDIK DALAM PERKARA PIDANA DI INDONESIA - Kristel Putri Regianna Br Pane; Gomgom T.P. Siregar; Syawal Amry Siregar (JURNAL PROINTEGRITA, 2021)
Law in Indonesia provides protection for a person's freedom, namely strictly prohibiting the deprivation of a person's freedom, with the existence of criminal sanctions. Freedom of a person is a universal right from the law. But a person's freedom has also been limited for the sake of law enforcement, as stated in article 50 of the Criminal Code which states that if someone acts on the basis of a law, he will not be penalized. If we connect it with the main duties and responsibilities of an investigator, who can arrest, detain and carry out the process of examining the criminal suspect, the investigator will carry out it according to the criminal procedure law, which eliminates the universally recognized rights of freedom of people. is a normative-empirical legal research, because the researcher uses statutory regulations as a study in solving problems, and the researcher also directly interviews the parties involved. The judiciary is a general court under the Supreme Court of the Republic of Indonesia which is the front guard of judicial power carry out the judiciary to achieve justice and law enforcement. The duties and powers of the Court, to receive, examine and decide on every case that falls within the jurisdiction of the court; Courts in Indonesia carry out an integrated function that is represented by judges. Judges bear the responsibility of bringing justice to the people and truth (searching for the truth) in order to create social integration, not creating social disintegration otherwise. Therefore it is hoped that judges can become independent judges, integrity, honesty, accountability, responsibility, openness, impartiality, and equal treatment before the law according to the main values​of the MA - RI. The obstacle factor faced by pretrial in controlling investigators is that there is no sanction for investigators who ignore pretrial decisions; the pretrial process is very short, negative interpretations of the rule of law, the behavior of individual judges, and different interpretations of judges.